2009
DOI: 10.3858/emm.2009.41.6.048
|View full text |Cite
|
Sign up to set email alerts
|

The orphan nuclear receptor SHP inhibits apoptosis during the monocytic differentiation by inducing p21WAF1

Abstract: Small heterodimer partner (SHP) is an atypical member of nuclear receptor superfamily that lacks a DNA-binding domain. In previous study, we showed that SHP, c-jun, p65 of NF-κB subunits, and p21WAF1 expression was increased during monocytic differentiaton with the exposure of human leukemia cells to a differentiation agent, PMA. In this study, c-Jun and p65 were shown to mediate the transcriptional activation of the SHP promoter. In addition, SHP induced the cell cycle regulatory protein levels and cooperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Indeed, while SHP was firstly described as transcriptional co-activator of NF-κB in several cell types [21][22][23][24], data from others support an anti-inflammatory role for this nuclear receptor [18][19][20]. Specifically, the molecular mechanisms by which SHP drives its antiinflammatory effects involved dual regulatory functions in a canonical transcription factor NF-κB signalling pathway, acting as both a repressor of transactivation of the NF-κB subunit p65…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, while SHP was firstly described as transcriptional co-activator of NF-κB in several cell types [21][22][23][24], data from others support an anti-inflammatory role for this nuclear receptor [18][19][20]. Specifically, the molecular mechanisms by which SHP drives its antiinflammatory effects involved dual regulatory functions in a canonical transcription factor NF-κB signalling pathway, acting as both a repressor of transactivation of the NF-κB subunit p65…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the heart, SHP expression blocks cardiac hypertrophy by interfering with GATA binding protein 6 (GATA6) signalling [17]. Concerning the role of SHP in the regulation of the inflammatory response, conflicting results have been reported in different contexts, i.e., SHP exerts anti-inflammatory effects [18][19][20], and SHP takes part in NF-κB activation [21][22][23][24]. In particular, the role of this nuclear receptor in cardiac glucose/lipid metabolism and inflammation is understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies revealed that when SHP specific ligands, 5-Cl-AHPN & 3-Cl-AHPC used alone or in combination, decreased cell proliferation and increased cell cycle arrest, and apoptosis in KG-1 AML cells [ 127 , 128 ]. Kim et al (2009) reported that treatment of leukemic (U937) cells with differentiation agents such as phorbol esters (PMA) have increased the levels of SHP, p21 WAF1 , and p65 of NF-κB subunits, suggesting how the expression of SHP increases the cellular survival of differentiating monocytes by transcriptional regulation of target genes of cell survival and differentiation [ 126 ]. In conclusion, SHPs play a vital role in tumorigenesis by modulating apoptosis, differentiation, and proliferation of tumor cells.…”
Section: Nrs In Hmmentioning
confidence: 99%
“…Another recent study shows that SHP expression was increased during monocytic differentiaton through c-Jun and p65 mediated transcriptional activation of the SHP promoter [40]. Interestingly, SHP protected differentiated monocytic cells from etoposide-induced cellular apoptosis through the induction and cytoplasmic sequestration of p21WAF1.…”
Section: Shp and Apoptosismentioning
confidence: 99%